A Co Relational Study On Academic Stress And Self-Esteem of students from Higher Secondary Schools Of Guwahati City - Hiranmayee Sarma; Bibi Bordoloi (Indian Journal of Psychiatric Nursing)
Higher secondary school stage is a stage of human development of the students that occurs between childhood and adulthood. Some sensitive factors like physical, mental, family, school, relationship and social factors influence on the students while learning. All people have minimum stress but excessive stress may cause anxiety and it's harmful for health. A co relational Study on Academic Stress and Self-Esteem among Higher Secondary Students in selected Schools of Guwahati City, Assam, India was conducted. Descriptive Co relational research design was used for the study and it was conducted on 250 students selected by using ‘multi-stage random sampling technique’ from five randomly selected Government Higher Secondary Schools of Guwahati city, Assam. Data were collected by using ‘Educational Stress Scale for Adolescents’ (ESSA) and ‘Rosenberg Self-Esteem Scale’. Results: Findings of the study revealed that out of 250 students, 169 students (67.6%) had moderate level of stress, 41 students (16.4%) had low level of stress and 40 students (16.0%) had high level of stress. Also that 177 students (70.8%) had moderate level of self-esteem, 37 students (14.8%) had low level of self-esteem and 36 students (14.4%) had high level of self-esteem. It was found that the level of academic stress and the level of self-esteem were negatively correlated with one another with r = -0.165 (P=0.004, <0.05) at.05 level of significance. Conclusion: Therefore, appropriate strategies for ‘stress management’ are highly recommended.